Gender socialisation and perception of gender by non-heteronormative people - Natalia Izydorczyk (Acta Universitatis Lodziensis: Folia Sociologica, 2024)
The submitted report focuses on the results of research carried out for a bachelor’s thesis titled “gender socialisation and perception of gender by non-heteronormative people”, in which the author focuses on gender socialisation of interviewees of non-heteronormative gender and/or sexual identity, their narrative about gender identity (in general, as well as personal sense) and gender expression, social roles expected of them as a result of their gender assigned at birth and restrictions they face in their daily life due to their gender identity. Social constructivism points out that masculinity and femininity are not constant but able-to-be-modified fluid products of everyday interactions. The process of constructing one’s gender connotates strictly with domineering discourse defining norms of masculine and feminine behaviour, which become overwhelmingly restrictive in regards to an individual’s thinking and actions. For this research, data was gathered from nine individual in-depth interviews supported by a script. During those interviews, interlocutors shared their personal stories about their gendered upbringing, explained what it means to identify with gender on a spectrum, indicated it through appearance and described their coming-out experiences.